Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-2443
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-Prosodic Indicators of Deception and Trust in Interview Dialogues

Abstract: We analyze a set of acoustic-prosodic features in both truthful and deceptive responses to interview questions, identifying differences between truthful and deceptive speech. We also study the perception of deception, identifying acousticprosodic characteristics of speech that is perceived as truthful or deceptive by interviewers. In addition to studying differences across all speakers, we identify variations in deception production and perception across gender and native language. We conduct machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…While there is a rich and growing body of research to support the above statement, it has to be acknowledged that many of the studies cited in this paper achieved their classification results under ideal laboratory conditions (e.g., scripted speech, high quality microphones, close-capture recordings, no background noise) [10,20,30,36,55,60,70,82,94,107], which may raise doubt about the generalizability of their inference methods. Also, while impressive accuracies have been reached, it should not be neglected that nearly all of the mentioned approaches still exhibit considerable error rates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While there is a rich and growing body of research to support the above statement, it has to be acknowledged that many of the studies cited in this paper achieved their classification results under ideal laboratory conditions (e.g., scripted speech, high quality microphones, close-capture recordings, no background noise) [10,20,30,36,55,60,70,82,94,107], which may raise doubt about the generalizability of their inference methods. Also, while impressive accuracies have been reached, it should not be neglected that nearly all of the mentioned approaches still exhibit considerable error rates.…”
Section: Discussionmentioning
confidence: 98%
“…Research has shown that the veracity of verbal statements can be assessed automatically [60,107]. Among other speech cues, acoustic-prosodic features (e.g., formant frequencies, speech intensity) and lexical features (e.g., verb tense, use of negative emotion words) were found to be predictive of deceptive utterances [67].…”
Section: Deception Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, all the SUs are stored in different files under different folders. Two kinds of labeling were proposed in [2,18], one is local deception and the other is global deception. It is known that not all of the components are deceptive when a lie is told.…”
Section: Segmentation Unit Organization and Labelingmentioning
confidence: 99%
“…We follow the work in [18] to figure out the acoustic indicators. All of the p values here are corrected by controlling the false discovery rate (FDR) at α = 0.05.…”
Section: Inter-subject Analysismentioning
confidence: 99%